Role of Diet in the Management of Psoriasis: A Review (AYUSHDHARA, 2022)
Psoriasis is an immune mediated, non infectious, chronic, inflammatory skin disease. It affects approximately 3% of the India’s population and the prevalence is much increasing. The exact cause of psoriasis is not known; however it’s believed both genetic and environmental factors including change in diet and lifestyle can be involved. Several factors are thought to aggravate flares of psoriasis. Psychological stress, physical injury, gut dysbiosis are the major triggering factors in the exacerbation of the disease. In Ayurved, all the skin diseases are described under the head ‘Kushta’. Psoriasis can be correlated with ‘Kitibha Kushta’ due to very much similarity in their symptoms. It is characterized by erythema or discoloration of skin, indurations, scaling and itching. Ayurved is a holistic science which not only aimed at prevention of disease but also cure of disease which is already manifested. Through proper diet and lifestyle prevention of the disease and treatment can be possible. It provides long lasting results and a better quality of life to the patients. In this article special emphasis should be given on the etiological factors of Psoriasis and role of diet in the Psoriasis management. According to Ayurved, incompatible diet and lifestyle (Virudhahara and vihara) is the most important cause of psoriasis. In this article various types of Virudhahara-vihara as per literature and in current era has been summarized. Objectives: 1. To estimate various etiological dietary factors in psoriasis. 2. To estimate role of diet in the management of psoriasis. Method: A comprehensive literature review was performed from modern as well as Ayurved literature, books, journals and website. Conclusion: Dietary modification is the most important treatment modality for preventing the onset of disease, reducing the disease severity and preventing the recurrence of psoriasis.